Synthesis and investigation of nanoscale magnesium carbonate stabilized with hyaluronic acid - A.V. Blinov; M.A. Pirogov; M.A. Yasnaya; A.S. Askerova; I.M. Shevchenko; S.V. Artyushin (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов)
As part of this work, the synthesis and study of nanoscale magnesium carbonate stabilized with hyaluronic acid was carried out. At the first stage, quantum chemical simulation of the interaction of magnesium carbonate nanoparticles with hyaluronic acid was carried out, as a result of which it was found that the addition of hyaluronic acid forms an energetically advantageous and chemically stable interaction. The most energetically advantageous (∆E = 462,410 kcal/mol) and chemically stable (n = 0,091 eV) is the interaction through a carboxyl group attached to C6 of the glucuronic acid residue. The synthesis was carried out by mixing solutions of magnesium acetate and hyaluronic acid, adding a solution of ammonium carbonate drop by drop at a rate of 30 ml per minute, stirring for 10 minutes at 700-1000 rpm. Further, the obtained samples were centrifuged for 5 minutes at 3000 rpm in a five-fold repeat and dried at 110°C for 8 hours. The powders were examined by powder diffractometry, scanning electron microscopy and infrared spectroscopy. As a result of X-ray phase analysis, the phase composition of the obtained sample was determined: anhydrous magnesium carbonate, magnesium carbonate crystallohydrate, the mineral «Artinite». Scanning electron microscopy showed that the sample consists of rod-shaped particles with a length of 5 to 10 microns, consisting of nanoparticles with a diameter of 20 to 100 nm. The analysis of the infrared spectra of nanoscale magnesium carbonate stabilized with hyaluronic acid, hyaluronic acid and nanoscale magnesium carbonate without using a stabilizer showed that deformation plane oscillations of the O-H group are observed in the infrared spectrum of nanoscale magnesium carbonate stabilized withhyaluronic acid in the range from 1300 to 1400 cm-1, which allows us to conclude that the interaction of nanosized magnesium carbonate with hyaluronic acid occurs through the hydroxyl group.